A kind of oxidation-resistant high-strength glass fiber and preparation method thereof

By performing multi-layer coating treatment and compound modification on glass fibers, the insufficient performance of existing antioxidant and sound-insulating damping materials in high humidity and high temperature environments is solved, and the long-term antioxidant and high-efficiency sound-insulating damping effects of glass fibers are achieved.

CN114804659BActive Publication Date: 2025-03-21MENGXIA NEW ENERGY VEHICLE MATERIALS (KUNSHAN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210556275.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-20
Publication Date
2025-03-21
Estimated Expiration
2042-05-20

AI Technical Summary

Technical Problem

The existing antioxidant treatment technology is difficult to be effective in high humidity and high temperature environments for a long time, and the existing sound insulation damping materials have single performance and insufficient safety and environmental protection.

Method used

By silver plating, deposition, copper plating and spraying the glass fibers, a piezoelectric conductive layer and an antioxidant film are formed, and combined with the use of chalone compounds and phosphite groups, the antioxidant and sound-insulating damping properties of the glass fibers are enhanced.

Benefits of technology

It realizes the long-term antioxidant performance of glass fiber in high humidity and high temperature environments, and improves its sound insulation and damping performance, meeting the requirements of safety and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003655064590000101
    Figure BDA0003655064590000101
  • Figure BDA0003655064590000111
    Figure BDA0003655064590000111
Patent Text Reader

Abstract

The invention discloses an anti-oxidation high-strength glass fiber and a preparation method thereof, and relates to the technical field of glass fiber. The present invention uses glass fiber as raw material, first sequentially performs silver plating, deposition treatment, copper plating, and spraying treatment, obtains a foam conductive network structure containing piezoelectric particles, can convert sound into electric current, and then into a heat energy mode, dissipates it, and makes the glass fiber have sound insulation damping; then further modified using 2'-hydroxy-4' (3-methyl-2-buteneoxy) acetophenone, 2,3-dihydroxy-4-ethoxybenzaldehyde, phosphorus trichloride and decanoic acid, so that the surface has antioxidant properties, and effectively resists hydrolysis. The anti-oxidation high-strength glass fiber prepared by the present invention has the effects of sound insulation damping and long-lasting antioxidant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass fibers, in particular to an oxidation-resistant high-strength glass fiber and a preparation method thereof. Background Art

[0002] Glass fiber has excellent properties such as good insulation, low thermal conductivity, and high strength, and is commonly used as a reinforcing material for coatings and cement. However, coatings are prone to oxidative degradation when exposed to high humidity and high temperatures for a long time. Existing antioxidant treatments mainly involve the addition of organic or inorganic antioxidants. However, organic antioxidants have weak hydrolysis resistance and lose their oxidative protection after a period of time, while inorganic antioxidants often face the problem of poor compatibility. Therefore, the present invention modifies glass fiber to impart long-lasting antioxidant properties and good dispersibility, making it an excellent coating antioxidant.

[0003] Furthermore, coatings have poor noise damping properties, leading to frequent noise interference and impacting quality of life. Existing sound insulation technologies typically use organic polymers as binders, combined with other sound-damping materials. However, these coatings not only increase energy consumption, but organic polymers are also flammable and prone to releasing harmful substances, making them unsuitable for safety and environmental protection, meeting increasingly stringent standards. Furthermore, most sound-damping materials offer only a single function, providing only sound insulation. Summary of the Invention

[0004] The object of the present invention is to provide an oxidation-resistant high-strength glass fiber and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an antioxidant high-strength glass fiber, the preparation method of the antioxidant high-strength glass fiber includes the following steps: using glass fiber as raw material, first performing silver plating treatment, deposition treatment, copper plating treatment, and spraying treatment in sequence to obtain piezoelectric conductive layer fiber, and then performing modification treatment to obtain an antioxidant layer.

[0006] Furthermore, the silver plating treatment is to pre-treat the glass fiber, immerse it in 3-mercaptopropylmethyldimethoxysilane, react for a predetermined time, immerse it in ethylene glycol solution, and then add ferric chloride solution, silver nitrate solution and reducing solution, and react for a period of time to obtain silver-plated fiber; the deposition treatment is to place the silver-plated fiber in an ethanol-ammonia mixture, add ethyl orthosilicate and coupling agent KH570, and obtain silica fiber after reaction; the copper plating treatment is to introduce hydrogen and copper acetylacetonate in an electric field-plasma environment, deposit for a period of time, calcine and wash to obtain foam copper fiber; the spraying treatment is to spray the piezoelectric powder precursor and gradient calcinate.

[0007] Furthermore, the modification treatment includes the following steps: mixing the piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone and glacial acetic acid, reacting for a predetermined time to obtain a modified matrix; then mixing the modified matrix with anhydrous ethanol, sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde to react to obtain chalcone fiber; then mixing the chalcone fiber, toluene and triethylamine, reacting for a period of time, adding the decanoic acid solution, continuing the reaction, then filtering and drying.

[0008] Furthermore, a method for preparing oxidation-resistant high-strength glass fiber includes the following preparation steps:

[0009] (1) Soaking the pretreated glass fiber in an impregnation solution 4 to 10 times the mass of the pretreated glass fiber, heating to 55 to 69° C., keeping warm for 3 to 6 hours, filtering, washing with deionized water 4 to 8 times, and drying at 90 to 110° C. and a vacuum degree of 20 to 40 kPa for 5 to 9 hours to obtain the modified glass fiber;

[0010] (2) placing the modified glass fiber in an ethylene glycol solution 25 to 35 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 0.9 to 1.5 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 150 to 160° C. and 100 to 200 rpm for 1 to 3 hours, adding a silver nitrate solution 13 to 16 times the mass of the modified glass fiber at 1 to 3 mL / min, and then adding a reducing solution 6 to 14 times the mass of the modified glass fiber at the same speed, reacting for 60 to 80 minutes, taking out, and washing with deionized water 5 to 9 times to obtain a silver-plated fiber;

[0011] (3) silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:15:2:3 to 1:32:7:5, stirred at 50-100 rpm for 8-14 minutes, and then 2-5 times the mass of the silver-plated fiber of ethyl orthosilicate was added. After reacting at room temperature for 11-15 hours, 0.1-0.3 times the mass of the silver-plated fiber of coupling agent KH570 and 4-8 times the mass of the silver-plated fiber of anhydrous ethanol were added. The reaction was continued for 47-50 hours, and the silica fiber was washed with anhydrous ethanol and deionized water for 3-5 times in sequence.

[0012] (4) Place the silica fiber in a plasma reactor under an external electric field of 25-40 V and evacuate to 5×10 -7 ~1×10 -6Pa, heated to 290-310°C in a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:1.7-1:2.5, and deposited for 44-68 minutes. After calcination at 400-480°C for 8-12 hours, the fiber was immersed in 20% hydrofluoric acid with a mass fraction of 0.9-2.8 times the mass of the silica fiber, washed at 25-35 kHz for 26-38 minutes, and dried at 40-50°C for 10-13 hours to obtain foamed copper fibers.

[0013] (5) spraying a piezoelectric powder precursor 0.2 to 0.5 times the mass of the foamed copper fiber onto the foamed copper fiber, heating to 240 to 300° C., calcining for 4 to 8 hours, then heating to 500 to 560° C., calcining for 8 to 14 hours, and continuing to heat to 750 to 810° C., calcining for 8 to 12 hours to obtain a piezoelectric conductive layer fiber;

[0014] (6) mixing the piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone and glacial acetic acid in a mass ratio of 1:28:0.3:0.1 to 1:34:0.6:0.1, reacting at 80 to 90° C. for 8 to 11 hours under nitrogen protection, washing with anhydrous ethanol and distilled water for 3 to 5 times in sequence, and freeze-drying at -18 to -6° C. for 24 to 28 hours to obtain a modified matrix;

[0015] (7) The modified substrate, anhydrous ethanol, a 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:1.7:4:0.7 to 1:3.3:7:0.9, stirred at 15 to 25°C and 100 to 200 rpm for 2.5 to 4.5 hours, allowed to stand in an ice bath for 30 to 46 minutes, filtered, and washed with anhydrous ethanol for 4 to 6 times to obtain chalcone fiber;

[0016] (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:2:0.03 to 1:5:0.03, and a phosphorus trichloride solution of 1.2 to 2.5 times the mass of the chalcone fiber was added at 60 to 70°C under nitrogen protection. After reacting for 30 to 42 minutes, the mixture was heated to 110 to 120°C and reacted for 1.5 to 3 hours. Then, a decanoid solution of 3.5 to 5.4 times the mass of the chalcone fiber was added and reacted for 3 to 6 hours. The mixture was filtered and dried at 40 to 50°C for 4 to 10 hours to obtain an antioxidant high-strength glass fiber.

[0017] Furthermore, the preparation method of the pretreated glass fiber in step (1) is as follows: after treating the glass fiber at 400-500°C for 1-3h, placing it in an acetone solution with a mass ratio of 1-5 times the mass of the glass fiber, wherein the mass ratio of acetone to deionized water in the acetone solution is 3:7, washing it at 30-40kHz for 20-30min, filtering it, and then placing it in a roughening solution with a mass ratio of 2-6 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillating it at the same frequency for 7-13min, and filtering it.

[0018] Furthermore, the diameter of the glass fiber is 10 to 20 μm.

[0019] Furthermore, the silver nitrate solution in step (2) is a mixture of silver nitrate and ethylene glycol in a mass ratio of 1:55.7; the composition of the reducing solution is: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest is deionized water.

[0020] Furthermore, the discharge voltage of the plasma reactor in step (4) is 18 to 22 kV, and the discharge frequency is 6 to 8 kHz.

[0021] Furthermore, the piezoelectric powder precursor in step (5) is a mixture of barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.1:0.2:0.04:5:0.4 to 1:0.3:0.4:0.06:11:0.4.

[0022] Furthermore, the phosphorus trichloride solution in step (8) is a mixture of phosphorus trichloride and toluene in a mass ratio of 1:1.9 to 1:3.1; and the decanoic acid solution is a mixture of decanoic acid, toluene, and triethylamine in a mass ratio of 1:1.9:0.2 to 1:2.6:0.2.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses glass fiber as raw material and sequentially covers a piezoelectric conductive layer and an anti-oxidation film to achieve anti-oxidation and sound insulation and damping properties.

[0025] First, the present invention performs a silver plating treatment, uses 3-mercaptopropylmethyldimethoxysilane for modification treatment, introduces mercapto groups on the surface of glass fibers, adsorbs silver ions through coordination reaction, and gradually grows to form silver nanowires under the action of polyols and nucleating agents, and overlaps with each other to form a network; then performs a deposition treatment, deposits and coats silica microspheres on the surface of the silver nanowires under the cross-linking action of a coupling agent; then performs a copper plating treatment, atomizes copper acetylacetonate, utilizes the reducing property of hydrogen plasma to form gaseous copper atoms, and after introducing an external electric field, generates charges on the surface of the silica, and at the same time, the gaseous copper atoms are impacted by space electrons and given charges. It obtains more energy and is effectively adsorbed on the surface of silica to form a copper coating. After calcination, the copper coatings bond with each other. Due to the ductility of silver, it reacts with the glass fiber and copper at the interface, promoting interface bonding, thereby forming connecting belts. The silica is then removed with acid to form foamed copper, which is entangled with the silver nanowires to form a conductive network. Then, a spraying treatment is carried out to adsorb the piezoelectric powder precursor in the foamed copper. While calcining to form piezoelectric powder, it adheres to the inner wall of the foamed copper at high temperature. Under sound or vibration, the piezoelectric powder generates voltage, converts the absorbed noise into current and dissipates it as heat along the conductive network, giving the glass fiber sound insulation and damping properties.

[0026] Secondly, the hydroxyl group of 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone is condensed with the hydroxyl group on the surface of the piezoelectric conductive layer and grafted onto the surface; the acetophenone group is then used to condense 2,3-dihydroxy-4-ethoxybenzaldehyde to obtain a chalcone compound, which can effectively remove free radicals generated by the degradation of the polymer coating under light and high temperature, so that the glass fiber has an antioxidant effect; the two hydroxyl groups of 2,3-dihydroxy-4-ethoxybenzaldehyde react with phosphorus trichloride to form a chlorinated dioxaphosphine heterocyclic compound, and then decanic acid reacts with chloride ions to obtain a phosphite group, forming a hindered phenol bisphenol radical that can terminate peroxyl radicals, which works together with the chalcone group to improve the antioxidant property of the glass fiber, and is capped with a long-chain alkyl group to prevent the hydrolysis of the antioxidant activity on the surface of the glass fiber, thereby enhancing its antioxidant effect. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0028] In order to more clearly illustrate the method provided by the present invention, the following examples are provided in detail. The test methods for various indicators of the oxidation-resistant high-strength glass fibers prepared in the following examples are as follows:

[0029] Anti-oxidation high-strength glass fiber, polymer emulsion, thickener, purified water, and defoaming agent were mixed in a mass ratio of 1:3:0.005:0.7:0.06, and applied to steel plates to the same thickness for antioxidant and sound insulation and damping effect tests.

[0030] Oxidation resistance: Yellowing resistance test was carried out according to GB / T23987, and the product was placed under 60°C temperature and 75% humidity conditions for 96 hours, and then yellowing resistance test was carried out again.

[0031] Sound insulation and damping: Refer to HG / T5058 for sound insulation and damping effect test.

[0032] Example 1

[0033] A method for preparing an oxidation-resistant high-strength glass fiber, the method for preparing an oxidation-resistant high-strength glass fiber mainly comprising the following preparation steps:

[0034] (1) After treating a glass fiber with a diameter of 10 μm at 400°C for 3 hours, the glass fiber is placed in an acetone solution with a mass ratio of acetone to deionized water of 3:7, washed at 30 kHz for 30 minutes, filtered, and then placed in a roughening solution with a mass ratio of 2 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water is 1:0.7:60, oscillated at the same frequency for 13 minutes, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber is immersed in an impregnation solution with a mass ratio of 4 times the mass of the pretreated glass fiber, heated to 55°C, kept warm for 6 hours, filtered, washed with deionized water 4 times, and dried at 90°C and a vacuum degree of 20 kPa for 5 hours to obtain a modified glass fiber;

[0035] (2) placing the modified glass fiber in an ethylene glycol solution 25 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 0.9 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 150°C and 100 rpm for 3 hours, adding a silver nitrate solution 13 times the mass of the modified glass fiber at 1 mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, and then adding a reducing solution 6 times the mass of the modified glass fiber at the same speed, reacting for 60 minutes, taking out, and washing with deionized water 5 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest being deionized water;

[0036] (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:15:2:3, stirred at 50 rpm for 14 minutes, and then ethyl orthosilicate (2 times the mass of the silver-plated fiber) was added. After reacting at room temperature for 11 hours, coupling agent KH570 (0.1 times the mass of the silver-plated fiber) and anhydrous ethanol (4 times the mass of the silver-plated fiber) were added. The reaction was continued for 47 hours, and the fiber was washed with anhydrous ethanol and deionized water three times in sequence to obtain silica fiber.

[0037] (4) Under an external electric field of 25 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 18 kV and a discharge frequency of 6 kHz, and the vacuum was evacuated to 5 × 10 -7 Pa, heated to 290 ° C in a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:1.7, and the deposition was carried out for 68 minutes. After calcination at 400 ° C for 12 hours, the fiber was immersed in 20% hydrofluoric acid with a mass fraction of 0.9 times the mass of the silica fiber, washed at 25 kHz for 38 minutes, and dried at 40 ° C for 13 hours to obtain foamed copper fibers;

[0038] (5) barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid are mixed in a mass ratio of 1:0.1:0.2:0.04:5:0.4 to obtain a piezoelectric powder precursor; 0.2 times the mass of the foamed copper fiber is sprayed onto the foamed copper fiber, and the mixture is heated to 240°C and calcined for 8 hours, then heated to 500°C and calcined for 14 hours, and then heated to 750°C and calcined for 12 hours to obtain a piezoelectric conductive layer fiber;

[0039] (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone and glacial acetic acid were mixed in a mass ratio of 1:28:0.3:0.1, reacted at 80°C for 11 hours under nitrogen protection, washed with anhydrous ethanol and distilled water three times in sequence, and freeze-dried at -18°C for 24 hours to obtain a modified matrix;

[0040] (7) The modified substrate, anhydrous ethanol, a 10% sodium hydroxide solution, and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:1.7:4:0.7, stirred at 15°C and 100 rpm for 4.5 hours, allowed to stand in an ice bath for 30 minutes, filtered, and washed with anhydrous ethanol four times to obtain chalcone fibers;

[0041] (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:2:0.03. Under nitrogen protection, a phosphorus trichloride solution with a mass ratio of 1.2 times that of the chalcone fiber was added at 60°C, and the mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:1.9. After reacting for 42 minutes, the mixture was heated to 110°C and reacted for 3 hours. Then, a decaned acid solution with a mass ratio of 3.5 times that of the chalcone fiber was added, and the mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:1.9:0.2. The mixture was reacted for 3 hours, filtered and dried at 40°C for 10 hours to obtain an antioxidant high-strength glass fiber.

[0042] Example 2

[0043] A method for preparing an oxidation-resistant high-strength glass fiber, the method for preparing an oxidation-resistant high-strength glass fiber mainly comprising the following preparation steps:

[0044] (1) After treating a glass fiber with a diameter of 15 μm at 450°C for 2 hours, the glass fiber is placed in an acetone solution 3 times the mass of the glass fiber, wherein the mass ratio of acetone to deionized water in the acetone solution is 3:7, washed at 35 kHz for 25 minutes, filtered, and then placed in a roughening solution 4 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillated at the same frequency for 10 minutes, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber is immersed in an impregnation solution 7 times the mass of the pretreated glass fiber, heated to 62°C, kept warm for 4.5 hours, filtered, washed with deionized water 6 times, and dried at 100°C and a vacuum degree of 30 kPa for 7 hours to obtain a modified glass fiber;

[0045] (2) placing the modified glass fiber in an ethylene glycol solution 30 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 1.2 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 155°C and 150 rpm for 2 h, adding a silver nitrate solution 14.5 times the mass of the modified glass fiber at 2 mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, then adding a reducing solution 10 times the mass of the modified glass fiber at the same speed, reacting for 70 min, taking out, and washing with deionized water 7 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest being deionized water;

[0046] (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:23.5:4.5:4, stirred at 70 rpm for 11 minutes, and then 3.5 times the mass of the silver-plated fiber of ethyl orthosilicate was added. After reacting at room temperature for 13 hours, coupling agent KH570 (0.2 times the mass of the silver-plated fiber) and 6 times the mass of the silver-plated fiber of anhydrous ethanol were added. The reaction was continued for 48.5 hours, and the fiber was washed with anhydrous ethanol and deionized water four times in sequence to obtain silica fiber.

[0047] (4) Under an external electric field of 32 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 20 kV and a discharge frequency of 7 kHz, and the vacuum was evacuated to 7.5 × 10 -7 Pa, heated to 300 ° C in a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:2.1, and the deposition was carried out for 56 minutes. After calcination at 440 ° C for 10 hours, the fiber was immersed in 20% hydrofluoric acid with a mass fraction of 1.8 times that of the silica fiber, washed at 30 kHz for 32 minutes, and dried at 45 ° C for 11.5 hours to obtain foamed copper fibers;

[0048] (5) Barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water, and citric acid were mixed in a mass ratio of 1:0.2:0.3:0.05:8:0.4 to obtain a piezoelectric powder precursor; 0.35 times the mass of the piezoelectric powder precursor was sprayed onto the foam copper fiber, heated to 270°C, calcined for 6 hours, then heated to 530°C, calcined for 11 hours, and further heated to 780°C, calcined for 10 hours to obtain a piezoelectric conductive layer fiber;

[0049] (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone and glacial acetic acid were mixed in a mass ratio of 1:31:0.45:0.1, reacted at 85°C for 9.5 seconds under nitrogen protection, washed four times with anhydrous ethanol and distilled water, and freeze-dried at -12°C for 26 hours to obtain a modified matrix;

[0050] (7) The modified matrix, anhydrous ethanol, a 10% sodium hydroxide solution, and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:2.5:5.5:0.8, stirred at 20°C and 150 rpm for 3.5 h, allowed to stand in an ice bath for 38 min, filtered, and washed with anhydrous ethanol five times to obtain chalcone fiber;

[0051] (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:3.5:0.03. Under nitrogen protection, a phosphorus trichloride solution with a mass ratio of 1.9 times that of the chalcone fiber was added at 65°C, and the mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:2.5. After reacting for 36 minutes, the mixture was heated to 115°C and reacted for 2.3 hours. Then, a decaned acid solution with a mass ratio of 4.5 times that of the chalcone fiber was added, and the mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:2.2:0.2. The mixture was reacted for 4.5 hours, filtered and dried at 45°C for 7 hours to obtain an antioxidant high-strength glass fiber.

[0052] Example 3

[0053] A method for preparing an oxidation-resistant high-strength glass fiber, the method for preparing an oxidation-resistant high-strength glass fiber mainly comprising the following preparation steps:

[0054] (1) After treating a glass fiber with a diameter of 20 μm at 500°C for 1 hour, the glass fiber is placed in an acetone solution 5 times the mass of the glass fiber, wherein the mass ratio of acetone to deionized water in the acetone solution is 3:7, washed at 40 kHz for 20 minutes, filtered, and then placed in a roughening solution 6 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillated at the same frequency for 7 minutes, and filtered to obtain a pretreated glass fiber; the pretreated glass fiber is immersed in an impregnation solution 10 times the mass of the pretreated glass fiber, heated to 69°C, kept warm for 3 hours, filtered, washed 8 times with deionized water, and dried at 110°C and a vacuum degree of 40 kPa for 9 hours to obtain a modified glass fiber;

[0055] (2) placing the modified glass fiber in an ethylene glycol solution 35 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution 1.5 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 160°C and 200 rpm for 1 hour, adding a silver nitrate solution 16 times the mass of the modified glass fiber at 3 mL / min, wherein the mass ratio of silver nitrate to ethylene glycol in the silver nitrate solution is 1:55.7, then adding a reducing solution 14 times the mass of the modified glass fiber at the same speed, reacting for 80 minutes, taking out, and washing with deionized water 9 times to obtain a silver-plated fiber; the composition of the reducing solution is: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest being deionized water;

[0056] (3) Silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:32:7:5, stirred at 100 rpm for 8 minutes, and then 5 times the mass of the silver-plated fiber was added with tetraethyl orthosilicate. After reacting at room temperature for 15 hours, 0.3 times the mass of the silver-plated fiber was added with coupling agent KH570 and 8 times the mass of the silver-plated fiber was added with anhydrous ethanol. The reaction was continued for 50 hours, and the silica fiber was washed with anhydrous ethanol and deionized water 5 times in sequence.

[0057] (4) Under an external electric field of 40 V, the silica fiber was placed in a plasma reactor with a discharge voltage of 22 kV and a discharge frequency of 8 kHz, and the vacuum was evacuated to 1×10 -6 Pa, heated to 310 ° C in a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:2.5, and the deposition was carried out for 44 minutes. After calcination at 480 ° C for 8 hours, the foamed copper fiber was immersed in 20% hydrofluoric acid with a mass fraction of 8 times that of the silica fiber, washed at 35 kHz for 26 minutes, and dried at 50 ° C for 10 hours.

[0058] (5) barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid are mixed in a mass ratio of 1:0.3:0.4:0.06:11:0.4 to obtain a piezoelectric powder precursor; 0.5 times the mass of the piezoelectric powder precursor of the foam copper fiber is sprayed onto the foam copper fiber, heated to 300°C, calcined for 4 hours, then heated to 560°C, calcined for 8 hours, and further heated to 810°C and calcined for 8 hours to obtain a piezoelectric conductive layer fiber;

[0059] (6) The piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4' (3-methyl-2-butenyloxy) acetophenone and glacial acetic acid were mixed in a mass ratio of 1:34:0.6:0.1, reacted at 90°C for 8 hours under nitrogen protection, washed with anhydrous ethanol and distilled water five times in sequence, and freeze-dried at -6°C for 28 hours to obtain a modified matrix;

[0060] (7) The modified substrate, anhydrous ethanol, a 10% sodium hydroxide solution, and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:3.3:7:0.9, stirred at 25°C and 200 rpm for 2.5 h, allowed to stand in an ice bath for 46 min, filtered, and washed with anhydrous ethanol six times to obtain chalcone fibers;

[0061] (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:5:0.03. Under nitrogen protection, phosphorus trichloride solution with a mass ratio of 2.5 times that of the chalcone fiber was added at 70°C. The mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution was 1:3.1. After reacting for 30 minutes, the mixture was heated to 120°C. After reacting for 1.5 hours, a decaned acid solution with a mass ratio of 5.4 times that of the chalcone fiber was added. The mass ratio of decaned acid, toluene and triethylamine in the decaned acid solution was 1:2.6:0.2. The mixture was reacted for 6 hours, filtered and dried at 50°C for 4 hours to obtain antioxidant high-strength glass fiber.

[0062] Comparative Example 1

[0063] Comparative Example 1 differs from Example 2 in that steps (1) and (2) are omitted, and step (3) is modified to: glass fiber, anhydrous ethanol, 25% ammonia water, and deionized water are mixed in a mass ratio of 1:23.5:4.5:4, stirred at 70 rpm for 11 minutes, and then 3.5 times the mass of the glass fiber of ethyl orthosilicate is added. After reacting at room temperature for 13 hours, 0.2 times the mass of the glass fiber of coupling agent KH570 and 6 times the mass of the glass fiber of anhydrous ethanol are added, and the reaction is continued for 48.5 hours. The silica fiber is washed four times with anhydrous ethanol and deionized water in sequence to obtain the silica fiber. The remaining preparation steps are the same as those in Example 2.

[0064] Comparative Example 2

[0065] The difference between Comparative Example 2 and Example 2 is that there is no step (3), and step (4) is changed to: under an external electric field of 32V, the silver-plated fiber is placed in a plasma reactor with a discharge voltage of 20kV and a discharge frequency of 7kHz, and the vacuum is evacuated to 7.5×10 - 7 Pa, heated to 300°C under a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:2.1, and deposition was performed for 56 minutes. After calcination at 440°C for 10 hours, the fiber was immersed in 20% hydrofluoric acid (mass fraction) 1.8 times the mass of the silver-plated fiber, washed at 30 kHz for 32 minutes, and dried at 45°C for 11.5 hours to obtain foamed copper fiber. The remaining preparation steps were the same as in Example 2.

[0066] Comparative Example 3

[0067] The difference between Comparative Example 3 and Example 2 lies in the difference in step (4). Step (4) is changed to: placing the silica fiber in a plasma reactor with a discharge voltage of 20 kV and a discharge frequency of 7 kHz, and evacuating the vacuum to 7.5×10 -7Pa, heated to 300°C under a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:2.1, and deposition was performed for 56 minutes. After calcination at 440°C for 10 hours, the fiber was immersed in 20% hydrofluoric acid (mass fraction) at a concentration 1.8 times the mass of the silica fiber, washed at 30 kHz for 32 minutes, and dried at 45°C for 11.5 hours to obtain foamed copper fibers. The remaining preparation steps were the same as in Example 2.

[0068] Comparative Example 4

[0069] The difference between Comparative Example 4 and Example 2 lies in the difference in step (4). Step (4) is changed to: under an external electric field of 32V, the silica fiber is placed in a container and vacuumed to 7.5×10 -7 Pa, heated to 300°C under a nitrogen atmosphere, hydrogen and copper acetylacetonate were introduced at a flow ratio of 1:2.1, and deposition was performed for 56 minutes. After calcination at 440°C for 10 hours, the fiber was immersed in 20% hydrofluoric acid (mass fraction) at a concentration 1.8 times the mass of the silica fiber, washed at 30 kHz for 32 minutes, and dried at 45°C for 11.5 hours to obtain foamed copper fibers. The remaining preparation steps were the same as in Example 2.

[0070] Comparative Example 5

[0071] Comparative Example 5 differs from Example 2 in that step (5) is omitted and step (6) is modified as follows: copper foam fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone, and glacial acetic acid are mixed in a mass ratio of 1:31:0.45:0.1, reacted at 85°C under nitrogen protection for 9.5 seconds, washed four times with anhydrous ethanol and distilled water, and freeze-dried at -12°C for 26 hours to obtain a modified matrix. The remaining preparation steps are the same as those in Example 2.

[0072] Comparative Example 6

[0073] Comparative Example 6 differs from Example 2 in that step (7) is omitted, and step (8) is modified as follows: a modified substrate, toluene, and triethylamine are mixed in a mass ratio of 1:3.5:0.03, and under nitrogen protection, a phosphorus trichloride solution (1.9 times the mass of the modified substrate) is added at 65° C., where the mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution is 1:2.5. After reacting for 36 minutes, the mixture is heated to 115° C. and reacted for 2.3 hours. Then, a hexadecanoic acid solution (4.5 times the mass of the modified substrate) is added, where the mass ratio of hexadecanoic acid, toluene, and triethylamine in the hexadecanoic acid solution is 1:2.2:0.2. The mixture is reacted for 4.5 hours, filtered, and dried at 45° C. for 7 hours to obtain an antioxidant high-strength glass fiber. The remaining preparation steps are the same as in Example 2.

[0074] Comparative Example 7

[0075] Comparative Example 7 differs from Example 2 in step (8), which is modified to: placing the chalcone fiber in a decanoid solution 4.5 times the mass of the chalcone fiber, wherein the mass ratio of decanoid acid, toluene, and triethylamine in the decanoid solution is 1:2.2:0.2, reacting for 4.5 hours, filtering, and drying at 45° C. for 7 hours to obtain the antioxidant high-strength glass fiber. The remaining preparation steps are the same as in Example 2.

[0076] Comparative Example 8

[0077] Comparative Example 8 differs from Example 2 in that step (8) is modified as follows: chalcone fiber, toluene, and triethylamine are mixed in a mass ratio of 1:3.5:0.03, and under nitrogen protection, a phosphorus trichloride solution (1.9 times the mass of the chalcone fiber) is added at 65° C., wherein the mass ratio of phosphorus trichloride to toluene in the phosphorus trichloride solution is 1:2.5. After reacting for 36 minutes, the mixture is heated to 115° C. and reacted for 2.3 hours to obtain an antioxidant high-strength glass fiber. The remaining preparation steps are the same as those in Example 2.

[0078] Effect Examples

[0079] Table 1 below shows the performance analysis results of coatings prepared using the antioxidant high-strength glass fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0080] Table 1

[0081]

[0082]

[0083] From the comparison of the experimental data of yellowing resistance before and after hydrolysis between the examples and the comparative examples, it can be found that the present product utilizes 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone, 2,3-dihydroxy-4-ethoxybenzaldehyde, phosphorus trichloride and decanoic acid to react to form a terminal long-chain compound, which prevents the hydrolysis of the antioxidant activity on the surface of the glass fiber and enhances its antioxidant effect. At the same time, a chalcone group-phosphite group is formed, and the two work together to improve the antioxidant property of the glass fiber. From the comparison of the experimental data of the weighted sound insulation increase and the loss factor at various temperatures between the examples and the comparative examples, it can be found that after the glass fiber is treated with silver plating, deposition, copper plating, spraying, etc., a foam conductive network containing piezoelectric ceramics is formed on the surface. Under sound or vibration, the piezoelectric powder generates voltage, converts the absorbed noise into current and dissipates it as heat along the conductive network, so that the glass fiber has sound insulation and damping properties.

[0084] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be encompassed therein. Any reference in a claim should not be construed as limiting the claim to which it relates.

Claims

1. An oxidation-resistant high-strength glass fiber, characterized in that: The method for preparing the anti-oxidation high-strength glass fiber comprises the following steps: using glass fiber as a raw material, firstly performing silver plating treatment, deposition treatment, copper plating treatment, and spraying treatment in sequence to obtain a piezoelectric conductive layer fiber, and then performing a modification treatment to obtain an anti-oxidation layer; The silver plating treatment is to soak the glass fiber in 3-mercaptopropylmethyldimethoxysilane after pretreatment, react for a predetermined time, soak it in ethylene glycol solution, then add ferric chloride solution, silver nitrate solution and reducing solution, react for a period of time to obtain silver-plated fiber; the deposition treatment is to place the silver-plated fiber in a mixed solution of ethanol and ammonia water, add tetraethyl orthosilicate and coupling agent KH570, and react to obtain silica fiber; the copper plating treatment is to introduce hydrogen and copper acetylacetonate in an electric field-plasma environment, deposit for a period of time, calcine and wash, and obtain foam copper fiber; the spraying treatment is to spray the piezoelectric powder precursor and gradient calcinate; The method for preparing the oxidation-resistant high-strength glass fiber comprises the following preparation steps: (1) After treating the glass fiber at 400-500°C for 1-3h, the glass fiber is placed in an acetone solution of 1-5 times the mass of the glass fiber, wherein the mass ratio of acetone to deionized water in the acetone solution is 3:7, washed at 30-40kHz for 20-30min, filtered, and then placed in a roughening solution of 2-6 times the mass of the glass fiber, wherein the mass ratio of ammonium fluoride, 37% hydrochloric acid, and deionized water in the roughening solution is 1:0.7:60, oscillated at the same frequency for 7-13min, filtered, and the pretreated glass fiber is obtained; the pretreated glass fiber is immersed in an impregnation solution of 4-10 times the mass of the pretreated glass fiber, heated to 55-69°C, kept warm for 3-6h, filtered, washed with deionized water for 4-8 times, dried at 90-110°C and vacuum degree of 20-40kPa for 5-9h, and the modified glass fiber is obtained; (2) placing the modified glass fiber in an ethylene glycol solution of 25 to 35 times the mass of the modified glass fiber, wherein the mass ratio of polyvinyl pyrrolidone to ethylene glycol in the ethylene glycol solution is 1:30, adding a ferric chloride solution of 0.9 to 1.5 times the mass of the modified glass fiber, wherein the mass ratio of ferric chloride to ethylene glycol in the ferric chloride solution is 1:2287, reacting at 150 to 160°C and 100 to 200 rpm for 1 to 3 hours, adding a silver nitrate solution of 13 to 16 times the mass of the modified glass fiber at 1 to 3 mL / min, and then adding a reducing solution of 6 to 14 times the mass of the modified glass fiber at the same speed, reacting for 60 to 80 minutes, taking out, and washing with deionized water for 5 to 9 times to obtain a silver-plated fiber; the silver nitrate solution is a mixture of silver nitrate and ethylene glycol at a mass ratio of 1:55.7; the reducing solution is composed of: 5 mL / L of nitric acid with a mass fraction of 68%, 7.5 g / L of glucose, 200 mL / L of ethanol, and the rest is deionized water; (3) The silver-plated fiber, anhydrous ethanol, 25% ammonia water, and deionized water were mixed in a mass ratio of 1:15:2:3-1:32:7:5, stirred at 50-100 rpm for 8-14 min, and then 2-5 times the mass of the silver-plated fiber of ethyl orthosilicate were added. After reacting at room temperature for 11-15 h, 0.1-0.3 times the mass of the silver-plated fiber of coupling agent KH570 and 4-8 times the mass of the silver-plated fiber of anhydrous ethanol were added, and the reaction was continued for 47-50 h. The fiber was washed with anhydrous ethanol and deionized water for 3-5 times in turn to obtain silica fiber. (4) Place the silica fiber in a plasma reactor under an external electric field of 25-40 V and evacuate to 5 × 10 -7 ~1×10 -6 Pa, heated to 290-310°C in a nitrogen atmosphere, introduced hydrogen and copper acetylacetonate at a flow ratio of 1:1.7-1:2.5, deposited for 44-68 minutes, calcined at 400-480°C for 8-12 hours, immersed in 20% hydrofluoric acid with a mass fraction of 0.9-2.8 times the mass of the silica fiber, washed at 25-35kHz for 26-38 minutes, and dried at 40-50°C for 10-13 hours to obtain foamed copper fibers; (5) Spraying a piezoelectric powder precursor of 0.2 to 0.5 times the mass of the foamed copper fiber onto the foamed copper fiber, heating to 240 to 300 ° C, calcining for 4 to 8 hours, then heating to 500 to 560 ° C, calcining for 8 to 14 hours, and then heating to 750 to 810 ° C, calcining for 8 to 12 hours to obtain a piezoelectric conductive layer fiber; (6) Mix the piezoelectric conductive layer fiber, anhydrous ethanol, 2'-hydroxy-4'(3-methyl-2-butenyloxy)acetophenone and glacial acetic acid in a mass ratio of 1:28:0.3:0.1~1:34:0.6:0.1, react at 80~90°C for 8~11h under nitrogen protection, wash with anhydrous ethanol and distilled water for 3~5 times in sequence, and freeze-dry at -18~-6°C for 24~28h to obtain a modified matrix; (7) The modified matrix, anhydrous ethanol, a 10% sodium hydroxide solution and 2,3-dihydroxy-4-ethoxybenzaldehyde were mixed in a mass ratio of 1:1.7:4:0.7-1:3.3:7:0.9, stirred at 15-25°C and 100-200 rpm for 2.5-4.5 h, allowed to stand in an ice bath for 30-46 min, filtered, and washed with anhydrous ethanol for 4-6 times to obtain chalcone fiber; (8) Chalcone fiber, toluene and triethylamine were mixed in a mass ratio of 1:2:0.03 to 1:5:0.

03. Under nitrogen protection, a phosphorus trichloride solution in an amount of 1.2 to 2.5 times the mass of the chalcone fiber was added at 60 to 70°C. The mixture was reacted for 30 to 42 minutes. The mixture was heated to 110 to 120°C. After reacting for 1.5 to 3 hours, a decaned acid solution in an amount of 3.5 to 5.4 times the mass of the chalcone fiber was added. The mixture was reacted for 3 to 6 hours. The mixture was filtered and dried at 40 to 50°C for 4 to 10 hours to obtain an antioxidant high-strength glass fiber.

2. The oxidation-resistant high-strength glass fiber according to claim 1, characterized in that: The diameter of the glass fiber in step (1) is 10-20 μm.

3. The oxidation-resistant high-strength glass fiber according to claim 1, characterized in that: The discharge voltage of the plasma reactor in step (4) is 18-22 kV, and the discharge frequency is 6-8 kHz.

4. The oxidation-resistant high-strength glass fiber according to claim 1, characterized in that: The piezoelectric powder precursor in step (5) is a mixture of barium acetate, calcium acetate, titanium dioxide, zirconium dioxide, deionized water and citric acid in a mass ratio of 1:0.1:0.2:0.04:5:0.4 to 1:0.3:0.4:0.06:11:0.

4.

5. The oxidation-resistant high-strength glass fiber according to claim 1, characterized in that: The phosphorus trichloride solution in step (8) is a mixture of phosphorus trichloride and toluene in a mass ratio of 1:1.9 to 1:3.1; the dodecanoic acid solution is a mixture of dodecanoic acid, toluene and triethylamine in a mass ratio of 1:1.9:0.2 to 1:2.6:0.2.

Citation Information

Patent Citations

  • Glass fiber reinforced high-strength engineering plastic and preparation method thereof

    CN112457659A